Carbon Capture Utilization (CCU) sebagai Generator Energi Listrik menggunakan Allam Cycle sebagai Upaya Dekarbonisasi Industri Migas - Izzati, Fifi; Ababil, Pijar Fitrah; Abror, Hadziqul (Journal of Sustainable Energy Development, 2023)
Along with the development and progress of human civilization, the need for electrical energy continues to increase. For this reason, new energy sources are needed so that energy needs can be met. Carbon dioxide (CO2) can be a new energy source obtained from industrial waste energy processing. CO2 is a type of emission that can cause the formation of greenhouse gas (GHG) emissions and contributes to global climate change. A 6% increase in emissions from 2020 results in emissions of 36.3 giga tons (Gt). One utilization of CO2 emissions that can be done is to convert CO2 emissions into electricity. The data analysis method is done by comparing the technical and economic parameters between the rankine power cycle using H2O as the working fluid and the Allam power cycle using CO2 as the working fluid. The results obtained are that the natural gas-fired Allam cycle has a net HHV and LHV efficiency of 53.17% and 58.90%, respectively. For the coal-fired Allam cycle, the net HHV and LHV efficiencies obtained were 48.88% and 51.44%, respectively. The economic analysis conducted is LCOE, IRR, and NPV. The economic analysis shows that the project is feasible in terms of electricity cost.